Peter Blastenbrei, Kriminalität in Rom 1560-1585, Tübingen 1995, ss. 317, Verlag Max Niemeyer. - Salmonowicz, Stanisław (Czasopismo Prawno-Historyczne, 1995)
Recenzja: Peter Blastenbrei, Kriminalität in Rom 1560-1585, Tübingen 1995, ss. 317, Verlag Max Niemeyer.